CSC782: Software Quality / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2018)
The course introduces the students to structured and systematic discipline of software quality engineering and management techniques. It covers, among others, quality in requirements and development process including software inspection, verification and testing as well as software metrics measurement techniques.